Heteroskedastic Proxy Vector Autoregressions - Helmut Lütkepohl; Thore Schlaak (ZBW - Leibniz Information Centre for Economics, 2021)
In proxy vector autoregressive models, the structural shocks of interest are identified by an instrument. Although heteroskedasticity is occasionally allowed for in inference, it is typically taken for granted that the impact effects of the structural shocks are time-invariant despite the change in their variances. We develop a test for this implicit assumption and present evidence that the assumption of time-invariant impact effects may be violated in previously used empirical models.
Keywords: C32; 330; Structural vector autoregression; proxy VAR; identification throughheteroskedasticity